Big Data Analytics and Open Banking: A New Paradigm for Shariah-Compliant Financial Ecosystems - Siti Kamiliyah Adriani; Mustofa Mustofa (Universitas Al-Qolam Malang, 2026)
The rapid growth of financial technologies has given rise to new paradigms in the banking sector, with Open Banking and Big Data Analytics emerging as key drivers of innovation. This paper explores how these technologies can reshape the Shariah-compliant financial ecosystem, offering new opportunities for enhancing transparency, efficiency, and customer engagement. Methodologically, this study employs a qualitative approach based on a systematic literature review to examine relevant secondary data. Open Banking, which enables secure sharing of financial data between institutions, combined with Big Data Analytics, offers powerful tools for optimizing financial services, improving risk management, and ensuring Shariah compliance. By analyzing the intersection of these two technologies within Islamic finance, this study highlights their potential to enhance operational effectiveness while adhering to Shariah principles. The research discusses the challenges and opportunities presented by this integration, including issues of data privacy, regulatory compliance, and the need for Shariah governance. Ultimately, this paper aims to provide a framework for understanding how Big Data and Open Banking can work together to foster more inclusive, efficient, and innovative Shariah-compliant financial ecosystems.